THE LANDSCAPE–ECONOMIC SYSTEM OF NEWLY IDENTIFIED ARCHAEOLOGICAL SITES IN THE FOOTHILL AREAS OF THE SANGZOR BASIN - Qulboyev N. S. (TARIXIY TADQIQOTLAR, 2026)
This study examines the landscape-economic system of newly identified archaeological sites located in the foothill areas of the Sangzor Basin. Through GIS and remote sensing analyses, the research reconstructs the relationship between settlements, seasonal camps, defensive structures, and economic features on the southern slopes of the Molguzar Range. The results demonstrate how ancient communities organized pastoral mobility, foothill agriculture, and water-resource management within a dynamic environmental setting. Spatial distribution patterns of the sites indicate the emergence of a stable and regionally integrated landscapeeconomic system in the Sangzor Basin.